Analisis Dan Perancangan Manajemen Bandwith Menggunakan Metode Hierarchial Token Bucket (HTB) Dan Filtering Layer7 Protocol Mikrotik - Khaidir, Muhammad; Noor, Muhammad Fajrian (Politeknik Indonusa Surakarta, 2022)
Internet users often complain about unstable internet connections and insufficient bandwidth, in fact the main problem is not because of insufficient bandwidth, but because there is no bandwidth management that regulates which packages are important and need to be prioritized. The research entitled